High prevalence and indexes of anti-John Cunningham virus antibodies in a cohort of Chinese patients with multiple sclerosis. Issue 3 (July 2018) - Lau, Alexander; Qiu, Wei; Kermode, Allan; Au, Cheryl; Ng, Angel; Wong, Adrian; Ma, Sze-Ho; Au, Lisa; Ma, Karen; Ip, Bonaventure; Mok, Vincent
We performed a cross-sectional study in 123 Chinese multiple sclerosis patients residing in Hong Kong to evaluate their anti-John Cunningham virus status using STRATIFY JCV DxSelect assays. Anti-John Cunningham virus antibody was present in 98/123 (80%) subjects, among which 75/98 (77%) had an anti-John Cunningham virus index ≥1.5. Anti-John Cunningham virus antibody seropositivity was not correlated with age, disease duration, Expanded Disability Status Scale scores, types of multiple sclerosis (relapsing vs progressive), or disease-modifying treatments used. We found a very high seroprevalence and index of anti-John Cunningham virus antibodies in Chinese multiple sclerosis patients, which may impact the risk assessment and recommendation of disease-modifying treatments in this population.